1997
DOI: 10.1046/j.1365-2141.1997.3353152.x
|View full text |Cite
|
Sign up to set email alerts
|

Fludarabine ability to down‐regulate Bcl‐2 gene product in CD5+ leukaemic B cells: in vitro/in vivo correlations

Abstract: CD5+ B‐chronic lymphocytic leukaemia (B‐CLL) and mantle cell lymphoma (MCL) in leukaemic phase are characterized by defects in cell death induction that primarily involves the Bcl‐2 family of genes. Fludarabine (9‐β‐D‐arabinofuranosyl‐2‐fluoradenine, F‐ara‐A) is a potent inducer of apoptosis in CLL cells. This study aimed to determine whether F‐ara‐A‐induced apoptosis might be related to Bcl‐2 modifications and to evaluate in vitro/in vivo correlations.  Peripheral blood lymphocytes from eight B‐CLL and four l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…B-CLL cells expressed significant amounts of Bax and Bcl-2 proteins, which did not significantly change with 2CdA treatment, according to Ref. 35 and it as previously found with Fara-A by most 4,15,36,37 but not all 38 authors. However, Bcl-2 overexpression prevented 2CdA-induced apoptosis in CEM 6 and Jurkat cells.…”
Section: Discussionsupporting
confidence: 76%
“…B-CLL cells expressed significant amounts of Bax and Bcl-2 proteins, which did not significantly change with 2CdA treatment, according to Ref. 35 and it as previously found with Fara-A by most 4,15,36,37 but not all 38 authors. However, Bcl-2 overexpression prevented 2CdA-induced apoptosis in CEM 6 and Jurkat cells.…”
Section: Discussionsupporting
confidence: 76%
“…Recently, it was reported that fludarabine could induce Bcl-2 down-regulation in cultured B-CLL cells and that antisense Bcl-2 oligonucleotides results in the induction of apoptosis in B-CLL cells. 14,37,70 In our study, the Bcl-2 and Bax expression was determined by RNase protection assay and FACS analysis. Using these methods, we found no significant changes (defined as more than 100% for mRNA expression levels or more than 1 log 10 concerning fluorescence intensity Leukemia for FACS analysis).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 It is yet unknown how the expression of the mem-bers of the Bcl-2 family are regulated and whether they can influence the drug sensitivity of B-CLL cells in vitro. 13,14 Caspase activation, following different stimuli, plays a key role in the apoptotic pathways by a specific cleavage of important cellular essential enzymes. 15,16 This activation mechanism seems to be under the control of dimerizing Bcl-2 family members.…”
Section: Introductionmentioning
confidence: 99%
“…71 Moreover, F-ara-A has been reported to downregulate Bcl-2 mRNA expression, thereby favoring apoptosis. 91 Finally, F-ara-A affects mitochondria but only as a late event, suggesting an indirect mechanism related to the p53-apoptotic pathway. 69 The different effects of F-ara-A and 2-CdA on mitochondria integrity may be related to the fact that 2-CdATP may accumulate more rapidly than F-ara-ATP in the mitochondria because it is converted with higher efficiency by mitochondrial dGK.…”
Section: Figurementioning
confidence: 99%